Neurosphere Based Differentiation of Human iPSC Improves Astrocyte Differentiation - Shuling Zhou; Karolina Szczesna; Anna Ochalek; Julianna Kobolák; Eszter Varga; Csilla Nemes; Abinaya Chandrasekaran; Mikkel Rasmussen; Susanna Cirera; Poul Hyttel; András Dinnyés; Kristine K. Freude; et al. (Stem Cells International)
Neural progenitor cells (NPCs) derived from human induced pluripotent stem cells (iPSCs) are traditionally maintained and proliferated utilizing two-dimensional (2D) adherent monolayer culture systems. However, NPCs cultured using this system hardly reflect the intrinsic spatial development of brain tissue. In this study, we determined that culturing iPSC-derived NPCs as three-dimensional (3D) floating neurospheres resulted in increased expression of the neural progenitor cell (NPC) markers, PAX6 and NESTIN. Expansion of NPCs in 3D culture methods also resulted in a more homogenous PAX6 expression when compared to 2D culture methods. Furthermore, the 3D propagation method for NPCs resulted in a significant higher expression of the astrocyte markers  GFAP and aquaporin 4 (AQP4) in the differentiated cells. Thus, our 3D propagation method could constitute a useful tool to promote NPC homogeneity and also to increase the differentiation potential of iPSC towards astrocytes.